(untitled) (Academicia Globe: Inderscience Research, 2022)
Traditionally, methods of teaching foreign languages distinguish between didactic and methodological principles. Principles are usually understood as fundamental methodological provisions that define the process of education and upbringing. Didactics defines the concept of the learning principle as follows: "learning Principles are the main normative provisions that should be followed in order for learning to be effective”.